Perlindungan Hukum Bagi Korban Tindak Pidana Perdagangan Orang (Human Trafficking) Dalam Persfektif Undang-Undang Nomor 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang - Al fajri; Deaf Wahyuni Ramadhani (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Human trafficking, also known as human trafficking, is a new form of transnational crime that is increasingly rampant. The crime of trafficking in persons is a modern form of human slavery, the crime of trafficking in persons, has expanded in the form of a network of organized and unorganized crimes. The crime of trafficking in persons even involves not only individuals but also corporations and state administrators who abuse their authority and power, According to Law Number 21 of 2007 concerning the Eradication of Trafficking in Persons Article 1 paragraph (1), human trafficking is the act of recruiting, transporting, sheltering, sending, transferring or receiving a person with the threat of violence, use of violence, kidnapping, detention, forgery, fraud, abuse of power or vulnerable position, debt entanglement or payment or benefit, This type of research is normative legal research, namely research that has the object of study on legal rules or rules. Legal protection for victims of human trafficking is very important, so various efforts are made so that they get the right to become useful human beings before returning to society. As well as efforts to empower economically and educationally so that victims are not trapped again in human trafficking. Adequate legal protection for victims of crime is not only a national issue, but also an international one, because this needs to receive serious attention, including victims of human trafficking. Victims of crime, who are basically the parties who suffer the most in a criminal act, do not receive as much protection as the law gives to criminals. As a result, after the perpetrator of the crime has been sentenced to criminal sanctions by the court, the victim's condition is not cared for.